CELIAC DISEASE IN CHILDREN - Lekovic, Zoran; Radlović, Vladimir; Mladenović, Marija; Dučić, Siniša; Bukva, Bojan; Rosić, Petar; Radlović, Nedeljko (Medical Research, 2023)
Celiac disease is a multisystemic autoimmune disease induced by gluten in wheat, rye and barley. It is characterized by polygenic predisposition, high prevalence in members of the white population (1%), especially in close relatives (5-15%), very heterogeneous expression and frequent association with other autoimmune diseases (3-10%), as well as selective deficiency of IgA and Down, Turner and Williams syndromes. The basis of the disease and the key finding in its diagnostics is symptomatic or asymptomatic inflammation of the small intestinal mucosa which resolves by gluten-free diet. Accordingly, the basis of the treatment involves an elimination diet, so that the disorder, if timely recognized and adequately treated, also characterizes an excellent prognosis.
Keywords: celiac disease, children, clinical forms, diagnostics, therapy